(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
Bakhmal district was located in the southeast of the Jizzakh region (Uzbekistan), and in the late XIX - Early XX Centuries, the name of this area was called Qora-qishloq. Before the conquest by Tsarist Russia in the last quarter of the 19th century, this land was part of the Emirate of Bukhara. The Bakhmal region, located in the southern part of the historical and geographical territory, which includes today’s Jizzakh, Syrdarya regions and the regions of Uratepa (Istaravshan), in ancient times and the early Middle Ages was called Ustrushona, served as one of the border regions between the historical and geographical lands of Ustrushona and Sogd.